Study of typical space wave-particle coupling events possibly related with seismic activity - 张振霞 王辰宇 申旭辉 李新乔 吴书贵 (Chinese physics B, 2014)
Based on the DEMETER satellite, we found two space wave-particle coupling events during February 2010 that took place in the range of the McIlwain parameter L （1.27-- 1.37）. There are strong spatial and temporal correlation between the particle bursts （PBs） and the electromagnetic disturbances of the coupling events. The two PBs show different energy spectrum characteristics, while the corresponding electromagnetic disturbances concentrated on different frequency ranges. In agreement with the prediction of the theory of wave-particle interaction, we conclude that the two wave-particle inter- actions can be probably explained as follows： one is electron-dominant precipitation with energy of 0.09 MeV,-~0.2 MeV induced by a VLF electromagnetic wave with the frequencies of 14 kHz,-20 kHz, and another is proton-dominant precip- itation with energies of 0.65 MeV--2.85 MeV induced by a VLF electromagnetic wave with the frequency of ≤ 100 Hz. For the first time, these particle bursts＇ origins, from electrons or protons detected by the Instrument for the Detection of Particles （IDP） on board, are inferred by theoretical calculation, although the instrument has no ability to identify the particle species.